Taxes and trust : from coercion to compliance in Poland, Russia and Ukraine - Berenson, Marc Phineas, 1971- (Cambridge : Cambridge University Press, 2018)
Taxes and Trust is the first book on taxes to focus on trust and the first work of social science to concentrate on how tax policy actually gets implemented on the ground in Poland, Russia and Ukraine. It highlights the nuances of the transitional Ukraine case and explains precisely how and why that'borderland' country differs from the more ideal-types of coercive Russia and compliance-oriented Poland. Through nine bespoke taxpayer surveys, an unprecedented bureaucratic survey and more than fifteen years of qualitative research, the book emphasizes the building and accumulation of trust to transition from a coercive tax state to a compliant one. The context of the book will appeal to students and scholars of taxation worldwide and to those who study Russia and Eastern Europe. This title is also available as Open Access.
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: Taxation -- Poland; Taxation -- Russia; Taxation -- Ukraine